THE THE NANOTECHNOLOGICAL WORK AND THE NECESSARY LEGAL METAMORPHOSIS:: How current risk societies can use a pluralistic regulatory environment to ensure that the worker does not fall back on human dignity. (Revista Direito em Debate, 2021)
Postmodernist techno-scientific evolution has achieved molecular levels of manipulation. Such finding is verified with the advent of the “Nanotechnological Revolution”, that is, the interaction and the production of nanoparticles - these corresponding to the billionth part of the meter. In this way, undoubtedly, the labor field becomes the target of this innovation that grows considerably - and without any certainty as to the consequences of the nano interaction with living beings. Consequently, concerns arise in the legal-labor field, mainly in the absence of specific regulatory frameworks. Therefore, the object of the present study is to demonstrate the importance of the performance of different actors for the protection of the human dignity of the worker, that is, the governmental sphere and the private sphere, in the face of the inertia of the Legislative Power. For that, the method used was the systemic-constructivist, as well as bibliographic reviews, through research of bases that do not compose the traditional Law. Thus, the harmonization of different poles is of paramount importance, since the need for non-retrogression in the human dignity of workers is considered. Also, formal and informal sources acting together are consolidating, mainly, in the face of a risk society that is characterized by the liquid nature of classic concepts - in particular, the Law itself (object of analysis).
Keywords: nanotechnologies; labor law; principle of non-setback; legal pluralism; human dignity.